A systematic review of e-commerce websites literature in 2010-2020 period - Özdemir, Kadir; Nacar, Ramazan (My University, 2022)
In parallel with the increasing e-commerce usage rates worldwide, academic papers on e-commerce have increased in the last decade. In this regard, in this study, the papers on e-commerce indexed in the Web of Science (WOS) database between 2010 and 2020 are examined and discussed by journals, published years, countries, sample size, main purposes, theories, variables and main findings. Therefore, 70 selected research articles were examined. The selection criteria of these articles are to be research articles and to collect data from consumers using e-commerce websites. Therefore, 70 selected articles were examined and evaluated by using the content analysis method. As a result of the analysis, selected articles are summarised in Appendix 1. The selected articles have some common inferences: the reputation of websites, size of websites, familiarity, perceived ease of use, recommendations, design, convenience, perceived usefulness, system quality, service quality and information quality in e-commerce positively influence perceived trust and purchase intention of consumers. Also, the perceived trust of the consumers positively affects their purchase and repurchase intention. Besides that, perceived usefulness, perceived ease of use, perceived value and perceived risk are important determinants of consumers' purchase and repurchase intention in e-commerce. Finally, perceived risk negatively affects the perception and purchase intention of consumers.
Keywords: İşletme